A new genus, with a new species, from Brazil (Acari : Prostigmata : Cunaxidae) - Martins Gomes de Castro, Tatiane Marie [UNESP]; Den Heyer, Jacob (Magnolia Press, 2008)
A new cunaxid genus from Brazil, Cunaxatricha gen. nov., is erected and its type species, Cunaxatricha tarsospinosa sp. nov. is described and figured. A key to the genera of the subfamily Cunaxinae, to which this new genus belongs, is provided.
Keywords: Bdelloidea; Cunaxinae; predatory mite; identification key; Taxonomy